Attention, cognitive control and motivation in ADHD: Linking event-related brain potentials and DNA methylation patterns in boys at early school age - Heinrich, Hartmut; Grunitz, Juliane; Stonawski, Valeska; Frey, Silke; Wahl, Simone; Albrecht, Bjoern; Goecke, Tamme W.; Beckmann, Matthias; Kornhuber, Johannes; Fasching, Peter; Moll, Gunther; Eichler, Anna (Scientific Reports, 2017)
In order to better understand the underpinnings of attention-deficit/hyperactivity disorder (ADHD), we targeted the relationship of attentional, cognitive control and motivational processes with DNA methylation patterns of 60 candidate genes in boys at early school age. Participants (6 to 8 years; N = 82) were selected from a German longitudinal cohort (FRANCES). ADHD-related behaviour was assessed via maternal ratings. Performance and event-related potential measures (inter alia Cue-P3 and Nogo-P3), which were recorded in a motivational go/nogo task, indicated diminished attentional orienting, reduced inhibitory response control and a larger motivational effect on performance in ADHD already at this relatively young age. Methylation patterns were analysed in buccal cell DNA with the Illumina HumanMethylation 450K array. For CpG sites at genes of the dopaminergic (COMT, ANKK1) and the neurotrophic (BDNF, NGFR) system, associations with the Nogo-P3 as well as ADHD symptom severity were found suggesting that these systems are involved in response control deficits in ADHD. Methylation effects related to both functional aspects and ADHD behaviour were also observed for DPP10 and TPH2. Epigenetic mechanisms may play a role in ADHD-associated deficits but findings need to be replicated in larger samples and are limited by the fact that only peripheral methylation could be considered.
EVALuna2:33560